2009
DOI: 10.1186/1755-8794-2-71
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling supports the hypothesis that human ovarian surface epithelia are multipotent and capable of serving as ovarian cancer initiating cells

Abstract: BackgroundAccumulating evidence suggests that somatic stem cells undergo mutagenic transformation into cancer initiating cells. The serous subtype of ovarian adenocarcinoma in humans has been hypothesized to arise from at least two possible classes of progenitor cells: the ovarian surface epithelia (OSE) and/or an as yet undefined class of progenitor cells residing in the distal end of the fallopian tube.MethodsComparative gene expression profiling analyses were carried out on OSE removed from the surface of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
169
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 79 publications
17
169
0
4
Order By: Relevance
“…While the OSE has been suggested to be largely composed of somatic stem cells (Bowen et al 2009), a number of recent studies have sought to attribute stem cell properties only to the subsets of cells on the ovary. The somatic stem cells in the OSE have been investigated in three distinct contexts: potential stem cells able to regenerate germ cells (Parte et al 2011, Patel et al 2013, Virant-Klun et al 2013a, potential stem cells that give rise to granulosa cells (Hummitzsch et al 2013), and more traditional somatic stem cells whose role is to replenish the OSE following ovulatory wounding (Szotek et al 2008, Motohara et al 2011, Usongo & Farookhi 2012, Auersperg 2013, Flesken-Nikitin et al 2013, Ng et al 2014.…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 99%
“…While the OSE has been suggested to be largely composed of somatic stem cells (Bowen et al 2009), a number of recent studies have sought to attribute stem cell properties only to the subsets of cells on the ovary. The somatic stem cells in the OSE have been investigated in three distinct contexts: potential stem cells able to regenerate germ cells (Parte et al 2011, Patel et al 2013, Virant-Klun et al 2013a, potential stem cells that give rise to granulosa cells (Hummitzsch et al 2013), and more traditional somatic stem cells whose role is to replenish the OSE following ovulatory wounding (Szotek et al 2008, Motohara et al 2011, Usongo & Farookhi 2012, Auersperg 2013, Flesken-Nikitin et al 2013, Ng et al 2014.…”
Section: Somatic Stem Cells Of the Osementioning
confidence: 99%
“…Ovarian cancer is the most lethal gynecological cancer in women because early detection is extremely difficult (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and because it is resistant to most chemotherapic drugs (15)(16)(17). The average lifespan after detection is 40.8 months for serous cancer, 21.3 months for clear cell carcinomas, 17.6 months for mucinous carcinomas and 50.9 months for endometrioid ovarian carcinomas (11).…”
Section: Introductionmentioning
confidence: 99%
“…It is subdivided according to the pathological appearance and molecular markers to four groups: serous-adenocarcinomas comprises 80% of the cancer and the rest are mucinous carcinomas, endometrioid carcinomas and clear cell carcinomas (reviewed in refs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Earlier it was reported that about 12-13% of total ovarian carcinomas are mucinous carcinomas, but recently, using new molecular markers, it was considered as only 2-3% of total ovarian carcinomas (16).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It is subdivided according to the pathological appearance and molecular markers to four groups: serous-adenocarcinomas comprises 80% of the cancer and the rest are mucinous carcinomas, endometrioid carcinomas and clear cell carcinomas (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%